Influence of pH, electrolytes and polymers on flocculation of kaolin particle - Nongkhran Chaiwong (2018)
Flocculation is the most important procedure prior to filter press process. Floc size and floc strength were determined as a function of pH, various electrolyte and polymer flocculant concentrations. The floc size and floc strength of kaolin suspension were investigated by laser diffraction technique and Dynamic Brookfield DV III+ viscometer, respectively. From the experimental results, addition of a high concentration of electrolyte and polymer flocculant gave larger floc size and floc strength. Furthermore, the floc size and floc strength increased with increasing of cation valency in the electrolytes and increasing of molecular weight in the polymers. Sedimentation rate of 25 ppm of polyvinyl alcohol (Low molecular weight) at pH 5.6 provided slightly slower than polyacrylamide (High molecular weight) at pH 8.3 due to polymer bridging mechanism. On the other hand, polyvinyl alcohol gave higher filtration rate than polyacrylamide. From the experiments, it can be concluded that pH, the concentration of electrolyte and polymers effect on sedimentation and filter rates.